Vitamin D status and functional parameters: A cross-sectional study in an older population - Mendes, J (2018)
The present study aims to clarify the association of vitamin D status with functionality, measured through gait speed and hand grip strength, in a sample of older adults, considering sex-specific characteristics and the potential confounding effect of lifestyle factors, disease, skin phenotype, season of blood collection and vitamin D supplementation. The Nutrition UP 65 cross-sectional study was conducted in a population-based sample of 1,425 older adults >= 65 years old. Serum levels of 25-hydroxyvitamin D were quantified through electro-chemiluminescence immunoassay. Multinomial logistic regressions were carried out using quartiles of gait speed and of hand grip strength as dependent variables. Participants at risk of vitamin D inadequacy (30.0-49.9 nmol/L) and deficiency (< 30.0 nmol/L) presented higher adjusted odds ratio of the lowest values of gait speed and hand grip strength than those with adequate vitamin D levels (>= 50.0 nmol/L). These associations were strongest among men at risk of vitamin D deficiency [adjusted odds ratio for the lowest quartile of gait speed = 3.24; 95% CI: 1.56-6.73 and for the lowest quartile of hand grip strength = 3.28; 95% CI: 1.47-7.31] than in women at risk of vitamin D deficiency [adjusted odds ratio for the lowest quartile of gait speed = 2.72; 95% CI: 1.37-5.41 and for the lowest quartile of hand grip strength = 1.56; 95% CI: 0.81-3.00]. In conclusion, in older adults, particularly in men, the risk of vitamin D deficiency was directly associated with the lowest values of gait speed and of hand grip strength. However, randomized controlled trials are needed to overcome the possibility of reverse causation and residual confounding. Present results emphasise the need for strategies to promote the reduction of the high prevalence of low vitamin D status among the Portuguese older adult population.